Mindfulness-based interventions with youth: A comprehensive meta-analysis of group-design studies. (August 2017) - Klingbeil, David A.; Renshaw, Tyler L.; Willenbrink, Jessica B.; Copek, Rebecca A.; Chan, Kai Tai; Haddock, Aaron; Yassine, Jordan; Clifton, Jesse
Abstract: The treatment effects of Mindfulness-Based Interventions (MBIs) with youth were synthesized from 76 studies involving 6121 participants. A total of 885 effect sizes were aggregated using meta-regression with robust variance estimation. Overall, MBIs were associated with small treatment effects in studies using pre-post ( g = 0.305, SE = 0.039) and controlled designs ( g = 0.322, SE = 0.040). Treatment effects were measured after a follow-up period in 24 studies ( n = 1963). Results demonstrated that treatment effects were larger at follow-up than post-treatment in pre-post ( g = 0.462, SE = 0.118) and controlled designs ( g = 0.402, SE = 0.081). Moderator analyses indicated that intervention setting and intervention dosage were not meaningfully related to outcomes after controlling for study design quality. With that said, the between-study heterogeneity in the intercept-only models was consistently small, thus limiting the amount of variance for the moderators to explain. A series of exploratory analyses were used to investigate the differential effectiveness of MBIs across four therapeutic process domains and seven therapeutic outcome domains. Small, positive results were generally observed across the process and outcome domains. Notably, MBIs were associated with moderate effects on the process variable of mindfulness in controlled studies ( n = 1108, g = 0.510). Limitations and directions for future research and practice are discussed.